Polyphenols in Crops, Medicinal and Wild Edible Plants From Their Metabolism to Their Benefits for Human Health - Brestic, Marian; Zivcak, Marek; Sytar, Oksana; Landi, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue "Polyphenols in Crops, Medicinal and Wild Edible Plants: From Their Metabolism to Their Benefits for Human Health" presents recent studies dealing with polyphenols isolated from different food sources in terms of nutraceutical, ethnobotanical, and pharmaceutical properties. The most recent techniques of analyses were used, e.g., high throughout metabolomics analyses as well as polyphenol-based fingerprinting to generate metabolic markers. The benefits of polyphenol extracts and isolated phenolic moieties related to human pathologies were also investigated.